2014
DOI: 10.1007/s11661-014-2393-z
|View full text |Cite
|
Sign up to set email alerts
|

Conventional and Multiscale Modeling of Microstructure Evolution During Laminar Cooling of DP Steel Strips

Abstract: Physical and numerical simulations of the hot rolling and laminar cooling of DP steel strips are presented in the paper. The objectives of the paper were twofold. Physical simulations of hot plastic deformation were used to identify and validate numerical models. Validated models were applied to simulate the manufacturing of DP steel strips. Conventional flow stress model and microstructure evolution model were used in the hot deformation part. The approach to the complex systems analysis based on global therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…The original crash box with stains transformed from the stamping, as well as the crash box after the test, are shown in this figure. All results presented in this section of the paper, as well as in publications (Kuziak and Pietrzyk, 2011) for hot rolling, (Pietrzyk et al, 2014b) for laminar cooling and (Ambrozinski et al, 2015) for stamping and crash tests, confirmed capabilities of the models to simulate the whole manufacturing chain for automotive parts.…”
Section: Simulation Of the Manufacturin Chainsupporting
confidence: 75%
See 2 more Smart Citations
“…The original crash box with stains transformed from the stamping, as well as the crash box after the test, are shown in this figure. All results presented in this section of the paper, as well as in publications (Kuziak and Pietrzyk, 2011) for hot rolling, (Pietrzyk et al, 2014b) for laminar cooling and (Ambrozinski et al, 2015) for stamping and crash tests, confirmed capabilities of the models to simulate the whole manufacturing chain for automotive parts.…”
Section: Simulation Of the Manufacturin Chainsupporting
confidence: 75%
“…For each process in Figure 3 models of various complexities were developed by the Authors. The models ranged from simple closed form equations describing selected parameters to advanced multiscale approaches combining FE code in macro scale with the Cellular Automata method in micro scale, see for example (Pietrzyk et al, 2014b). Selection of the best model of each process in the cycle for the purpose of the optimization of the manufacturing technology is described in (Rauch et al, 2014a).…”
Section: Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Typical hot strip rolling mill composed of the furnace, reverse rouging stand, six stand continuous finishing train, laminar cooling and coiler was considered. The laminar flow cooling system is composed of two sections with 40 boxes in each section, see [25] for details. The length of each box is 1 m. The sections are divided into eight zones of three types: intensive, normal, and trimming zone.…”
Section: Various Finishing Rolling Temperaturesmentioning
confidence: 99%
“…Finite element model of the laminar cooling and coiling processes is described in (Pietrzyk et al, 2014). Phase transformation models described in the present paper were implemented into the FE code and current, local changes of the temperature were used in the calculations of the kinetics of transformation.…”
Section: Laminar Cooling and Coiling Processesmentioning
confidence: 99%